Synthesis, Characterization And Antibacterial Activity Of Azitidinone Containing Compounds - V. Talaviya, Purav; J., A. Chaudhari (International Journal of Psychosocial Rehabilitation, 2020)
The Schiff bases, 4-(substituted benzylidene amino)-N-(5-methylisoxazol-3-yl) benzene sulfonamide (3a-f), were prepared from sulphamethoxazole (1) and aromatic aldehydes (2a-f), and then they were condensed with chloroacetyl chloride to yield 2-azitidinone derivatives, namely 4-(3-chloro-2-oxo-4-arylazetidin-1-yl)-N-(5-methylisoxazol-3-yl) benzene sulfonamide (4a-f). The (4a-f) were further treated with 1H-imidazole to 4-(3-(1H-imidazol-1-yl)-2-oxo-4-arylazetidin-1-yl)-N-(5-methylisoxazol-3-yl)benzenesulfonamide (6a-f). The derivatives (3a-f), (4a-f), and (6a-f) were characterized by elemental content and spectral features. Their antibacterial activity has also been monitored against common microbes.